Hand-assisted laparoscopic Hassab’s procedure for esophagogastric varices with portal hypertension - Takashi Kobayashi; Kohei Miura; Hirosuke Ishikawa; Daiki Soma; Zhengkun Zhang; Takuya Ando; Kizuki Yuza; Yuki Hirose; Tomohiro Katada; Kazuyasu Takizawa; Masayuki Nagahashi; Jun Sakata; et al. (Surgical Case Reports)
Abstract Background Laparoscopic surgery for patients with portal hypertension is considered to be contraindicated because of the high risk of massive intraoperative hemorrhaging. However, recent reports have shown hand-assisted laparoscopic surgery for devascularization and splenectomy to be a safe and effective method of treating esophagogastric varices with portal hypertension. The aim of this study is to evaluate the efficacy of hand-assisted laparoscopic devascularization and splenectomy (HALS Hassab’s procedure) for the treatment of esophagogastric varices with portal hypertension. Case presentation From 2009 to 2016, seven patients with esophagogastric varices with portal hypertension were treated with hand-assisted laparoscopic devascularization and splenectomy in our institute. Four men and three women with a median age of 61 years (range 35–71) were enrolled in this series. We retrospectively reviewed the medical records for the perioperative variables, postoperative mortality and morbidity, and postoperative outcomes of esophagogastric varices. The median operative time was 455 (range 310–671) min. The median intraoperative blood loss was 695 (range 15–2395) ml. The median weight of removed spleen was 507 (range 242–1835) g. The conversion rate to open surgery was 0%. The median postoperative hospital stay was 21 (range 13–81) days. During a median 21 (range 3–43) months of follow-up, the mortality rate was 0%. Four postoperative complications (massive ascites, enteritis, intra-abdominal abscess, and intestinal ulcer) were observed in two patients. Those complications were treated successfully without re-operation. Esophagogastric varices in all patients disappeared or improved. Bleeding from esophagogastric varices was not observed during the follow-up period. Conclusion Although our data are preliminary, hand-assisted laparoscopic devascularization and splenectomy proved an effective procedure for treating esophagogastric varices in patients with portal hypertension.